Practical aspects of risk management of threat in information system - Скиба, Андрей Владимирович; Архипов, Александр Евгеньевич (Ukrainian Information Security Research Journal, 2015)
One of the most urgent problems of research and exploitation of information security systems is the evaluation ofthe generalized index of protection information system, as which is often known as integral risk. This scalar measure is a reflection of a set of partial risks (risks of attacks,threats risk, vulnerability risk of individual elements of information systems (IS)). In the paper conditions ofcorrect display of partial risks in integral is stated. Considered mechanisms of risk occurrence, processes of thedestructive consequences of threats and formation oflosses. The problems, which arising from the evaluationof probability parameters of risk and determine the levelof losses in the case of multiple threats. The techniqueprioritize information assets IP according to their vulnerability.